What is Intuitive Interaction? Balancing Users' Performance and Satisfaction with Natural User Interfaces - Macaranas, Anna; Antle, Alissa N.; Riecke, Bernhard E. (Interacting with Computers, 2015)
Designers of Natural User Interfaces (NUIs) are faced with several challenges when creating interaction models for controlling applications, including the wide range of possible input actions and the lack of affordances which they can use to design controls. In order to contribute to the development of design guidelines in this design space, we conducted an exploratory, mixed methods study. We investigated three top-down approaches to designing intuitive interactional mappings for the same whole body system. These were metaphoric, isomorphic and “everyday” or conventional. In order to identify some of the benefits and limitations of each approach, we compared the designs based on measures of usability, intuitiveness and engagement with the material represented in a whole body installation. From our study, we found that while the metaphoric design enhanced users’ performance completing tasks, the lack of discoverability of the interaction model left them feeling incompetent and dissatisfied. We found that the isomorphic design enabled users to focus on tasks rather than learning how to how to use the system. Conversely, designs based on previous conventions had to be learned, had a time cost for the learning and negatively impacted users’ engagement with content. For tasks and controls that can be designed based on an image schematic input action, users performed most accurately with the metaphoric design. There are benefits and limitations to each approach to designing to support intuitive interaction. We conclude with preliminary design considerations, suggest ways to balance performance with high user satisfaction depending on contextual design goals and question a single definition of intuitive intuition within whole body interface design.
Keywords: Natural User Interfaces, metaphor, intuitive interaction, design guidelines; Riecke; Riecke_2015; alissa-antle; anna-macaranas; bernhard-riecke; journalPaper